NHX Gene Family in Camellia sinensis: In-silico Genome-Wide Identification, Expression Profiles, and Regulatory Network Analysis - Paul, Abhirup; Chatterjee, Archita; Subrahmanya, Shreya; Shen, Guoxin; Mishra, Neelam (Frontiers in Plant Science, 2021)
Salt stress affects the plant growth and productivity worldwide and NHX is one of those genes that are well known to improve salt tolerance in transgenic plants. It is well characterized in several plants such as Arabidopsis and cotton however not much is known about NHXs in tea plant. In the present study, NHX genes of tea were obtained through a genome wide search using Arabidopsis thaliana as reference genome. Out of the 9 NHX genes in tea, 7 genes were localized in vacuole while the remaining 2 genes were localized in the endoplasmic reticulum (ER) (TEA014468.1) and plasma membrane (PM) (TEA006997.1) respectively. Furthermore, phylogenetic relationships along with structural analysis which includes gene structure, location as well as protein conserved motifs and domains, were systematically examined and further, predictions were validated by the expression analysis. The dN/dS values show that the majority of tea NHX genes are subjected to strong purifying selection under the course of evolution. Also, functional interaction was carried out in C. sinensis based on the orthologous genes in Arabidopsis. The expression profiles linked to various stress treatments revealed wide involvement of NHX genes from tea in response to various abiotic factors. This study provides the targets for further comprehensive identification, functional study, and also contributed for a better understanding of the NHX regulatory network in C. sinensis.